BURDEN OF THE PAST, J. KRISHNAMURTHY - Singh, Khushboo; Chandra, Ritu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Generally, the way we live our lives, we rarely get solitude. Even if we are alone, then many kinds of influences, experiences, knowledge, and memories, worries, struggles, and sorrows surround us from all sides. Due to these things, our mind becomes more and more dull, stupid and insensitive. It goes on living the same routine life every day. So, are we ever able to be alone in the true sense? Or are we always carrying the burden of the past with us? An attempt has been made to talk about these questions in this article, in which the main points taken are, calm mind, thoughtless state and expansion and dispersion, discipline, silence.